Legacy of COVID-19 Innovations: Strengthening African Primary Health Care through Pandemic Innovations - Ngongoni, Chipo Nancy; Wasswa, William; Chibi, Moredreck (Sustainability, 2023)
The COVID-19 pandemic led to a global surge of health care innovations aimed at curbing the pandemic. Some of the innovations were newly developed whereas others were modiﬁcations of existing technologies to suit the COVID-19 response. With the world achieving some level of normalcy, the question is what will become of these innovations. This study reviewed and analysed 1003 innovations that were utilised for the COVID-19 response to assess if they are still being utilised to strengthen health systems. The paper goes on to identify, proﬁle and showcase 48 innovations and trace their evolution to support and strengthen Primary Health Care. Through this analysis and narration, four strategic pillars of collaboration, governance, innovation design and strategy emerge as factors that help explain the successful integration of these innovations in Primary Health Care. Under these pillars emerged nine key aspects of strategic inter-industry collaborations, standardisation and supportive policies, minimalistic and modular designs, off-grid capabilities, interoperability, data infrastructure, interoperability, data analytics including security and privacy, and the design of technology around ecosystems and platforms. The overall aim of this study is to inform the dynamics around the improvement of scaling and increase the sustainability of innovations across the African region to strengthen health systems and promote innovation.
Keywords: COVID-19 technologies; Primary health care; Innovation; Health innovation ecosystems